How the pandemic shaped teenagers’ views on violence: exploring the complexities of post-confinement attitudes - Rodríguez, Juan Carlos; Rodríguez-Góngora, Josefina; Rodríguez-Rodríguez, José Antonio (Frontiers in Education, 2023)
Violent extremism is a complex and pressing issue that affects all sectors of society, and demands research aimed at preventing and transforming violent behavior. This study presents the results of a questionnaire consisting of 34 items that was administered to 1,169 teenagers from two secondary schools in Almería and Madrid (Spain), immediately after the end of COVID-19 confinement measures. The primary objective of the study is to analyze the ideas that teenagers hold regarding violent extremism and pro-violent attitudes, as well as their relationship with other factors such as digital consumption, interpersonal relationships, and the socio-demographic situation of their families. Direct interventions were carried out with the students in the participating educational centers to collect the data. The findings reveal that variables such as gender, number of siblings, and religious practice influence violent extremism, while nationality is not a significant factor. The study also identifies several factors that contribute to the prevalence of extremist and pro-violent attitudes, and a moderation analysis is conducted using the mother's level of education as a moderator variable. Based on the results, the study recommends further research to better understand the development of violent attitudes and behaviors, as well as the implementation of family and personal support programs aimed at promoting healthy adolescent development.